2019
DOI: 10.4103/ijri.ijri_353_19
|View full text |Cite
|
Sign up to set email alerts
|

Imaging diagnosis of Crouzon syndrome in two cases confirmed on genetic studies - with a brief review

Abstract: Crouzon syndrome is the most common form of craniofacial dysostosis, characterised by a classical triad of abnormal skull shape, abnormal facies, and exophthalmos. The clinically overt dental abnormalities in these patients, distracts clinicians from the developmental neurological defects and therefore this entity remains relatively under - highlighted in radiology literature. We report and highlight the role of imaging in diagnosis of Crouzon syndrome in two patients, and discuss the relevant differential dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The ectoderm covers a vital role in brain embryogenesis; therefore, its alteration in craniosynostosis syndromes can lead to brain anomalies such as schizencephaly or Dandy-Walker syndrome, as shown in this case [5] , [6] , [7] , [8] , [9] . Several mutations in transcription-derived growth factors have been associated with craniosynostosis syndromes, such as TWIST, FBN1, FGFR 1, 2, 3, tumor growth factor-b1, and b2 [10] . Particularly, Crouzon syndrome is caused by mutations in FGFR 2 or FGFR 3 [10] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ectoderm covers a vital role in brain embryogenesis; therefore, its alteration in craniosynostosis syndromes can lead to brain anomalies such as schizencephaly or Dandy-Walker syndrome, as shown in this case [5] , [6] , [7] , [8] , [9] . Several mutations in transcription-derived growth factors have been associated with craniosynostosis syndromes, such as TWIST, FBN1, FGFR 1, 2, 3, tumor growth factor-b1, and b2 [10] . Particularly, Crouzon syndrome is caused by mutations in FGFR 2 or FGFR 3 [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Several mutations in transcription-derived growth factors have been associated with craniosynostosis syndromes, such as TWIST, FBN1, FGFR 1, 2, 3, tumor growth factor-b1, and b2 [10] . Particularly, Crouzon syndrome is caused by mutations in FGFR 2 or FGFR 3 [10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Imaging has been found to be beneficial in the early diagnosis of Crouzon syndrome. 5 Hypercementosis, the excessive formation of cementum above what is deemed normal, has been documented in a case of Crouzon syndrome in a 35-yearold female. 6 It has been reported that generalized cases of hypercementosis are rare.…”
Section: E T T E R T O T H E E D I T O R Hypercementosis Development In a Patient With Crouzon Syndromementioning
confidence: 99%